Modeling Nitrogen Movement in Rice Irrigated Using Sewage Water - Jasuja, Hemant; Shakya, S K; Singh, K G (Journal of Agricultural Engineering, 2006)
A numerical model is described to simulate water and nitrogen transport and transformations under transient soil water flow conditions. The nitrogen transformation processes considered were nitrification, denitrification, immobilization, mineralization, and ionic exchange of ammonium. The model was evaluated using experimental data from a lysimeteric study. Two sets of lysimeters were irrigated with sewage water, whereas, one set was irrigated with tubewell water. Each set had four lysimeters having depths of 1.2, 1.5, 1.8, and 2.0m. Soil and leachate samples were collected and analyzed at regular intervals for NH4+ -N and NO3-N. Model predictions of NH4+-N and NO3-N were in close agreement with the observed values except for 37th day observations for NH4+-N and 110th day observations in case ofNO3-N. To evaluate the model performance a paired t test and root mean square error (RMSE) methods were applied. The RMSE values ranged from 0.1 to 3.9 and 0.05 to 2.55 for the ammonium and nitrate distributions, respectively.